Social Responsibility in E-Commerce: Reflection on Customer’s Satisfaction and Loyalty in Internet Promotion of Tourist Services - Maric, Tijana Jovica; Nikolic, Ivica; Maric, Radenko Milos; Dzeletovic, Milenko (Industrija, 2015)
The aim of this paper is to determine, based on theoretical and empirical research, whether and to what extent the application of the social responsibility concept in e-commerce and marketing affects the satisfaction and loyalty of customers opting for on-line purchase. The main task is to use the case of global on-line buying and selling of tourist services to test the null hypothesis on the existence of a statistically significant correlation between the concept of social responsibility and customer’s satisfaction and loyalty. Empirical research was conducted on a sample of 409 respondents from selected countries: Serbia, Turkey, Egypt, Italy and Spain. Contingency coefficient and Pearson’s correlation coefficient were used for the interpretation of the results and determination of the degree of correlation between these variables. The research results indicated a significant statistical correlation between the concept of social responsibility and customer’s satisfaction and loyalty. These results served as a basis for proposed measures necessary for defining the model of social corporate social responsibility in e-commerce, which will be generally binding for all on-line advertisers. Suggestions for future research are provided in the paper.